2013
DOI: 10.1161/circresaha.113.300764
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Conditioning

Abstract: Myocardial conditioning is an endogenous cardioprotective phenomenon that profoundly limits infarct size in experimental models. The current challenge is to translate this paradigm from the laboratory to the clinic. Accordingly, our goal in this review is to provide a critical summary of the progress toward, opportunities for, and caveats to, the successful clinical translation of postconditioning and remote conditioning, the 2 conditioning strategies considered to have the broadest applicability for real-worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 141 publications
(169 reference statements)
1
50
0
Order By: Relevance
“…However, reperfusion of the ischemic myocardium may itself cause damage to the heart. This ischemiareperfusion injury involves direct cardiomyocyte death and also myocardial 8 stunning, arrhythmias and the "no reflow" phenomenon (Gerczuk and Kloner, 2012;Jennings 2013;Ovize et al, 2013). Several approaches including pre-, post-, and remote-ischemic conditioning and several pharmacological therapies including immune modulation have been promising in both preclinical and clinical models.…”
Section: The Complement System and Myocardial Ischemia-reperfusion Inmentioning
confidence: 99%
“…However, reperfusion of the ischemic myocardium may itself cause damage to the heart. This ischemiareperfusion injury involves direct cardiomyocyte death and also myocardial 8 stunning, arrhythmias and the "no reflow" phenomenon (Gerczuk and Kloner, 2012;Jennings 2013;Ovize et al, 2013). Several approaches including pre-, post-, and remote-ischemic conditioning and several pharmacological therapies including immune modulation have been promising in both preclinical and clinical models.…”
Section: The Complement System and Myocardial Ischemia-reperfusion Inmentioning
confidence: 99%
“…[10][11][12] Therefore, additional interventions and treatments on top of timely reperfusion are still needed to reduce infarct size and improve the clinical outcome of patients with AMI. [13][14][15][16][17][18][19][20] Apart from acute STEMI (type 1 myocardial infarction), additional cardioprotection is also sought in elective PCI with the aim to reduce periprocedural myocardial infarction (type 4a) and in surgical coronary revascularization with the aim to reduce perioperative myocardial infarction (type 5) 21 ; in some studies, cardioprotection was also sought in major cardiovascular surgery other than coronary artery bypass grafting (CABG).…”
mentioning
confidence: 99%
“…The translation of cardioprotection by the conditioning phenomena and by drugs that recruit part of their signaling to the clinical arena has been difficult to date. [13][14][15][16][17][18][19] Although there are several positive proof-of-concept studies for each of the conditioning phenomena, no phase III study has yet reported a better clinical outcome as the primary end point. With the neutral results of 2 recent phase III trial in cardiosurgical patients, that is, ERICCA (Effect of Remote Ischemic Preconditioning on Clinical Outcomes in CAGB Surgery) 37 and RIPHeart (Remote Ischemic Preconditioning in Heart Surgery), 38 and also a number of recent neutral trials which used drugs to recruit signaling steps of the conditioning phenomena in patients with AMI, that is, CIRCUS (Does Cyclosporine Improve Clinical Outcome in ST Elevation Myocardial Infarction Patients) 39 and CYCLE (Cyclosporine A in Reperfused Myocardial Infarction), 40 disappointment and frustration prevail.…”
mentioning
confidence: 99%
“…Low-pressure reperfusion (variant of post-conditioning) at the time of reperfusion also merits consideration for post-ischemic myocyte protection [143]. However, cytoprotection potential of these interventions in humans remains controversial [144,145].…”
Section: Non-pharmacologic Approachmentioning
confidence: 99%